2006
DOI: 10.1158/0008-5472.can-05-4329
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Access for Prevention and Therapy of Mammary Tumors

Abstract: In cancer patients and in those at high risk, systemic exposure to agents for therapy or prevention is accompanied by undesirable side effects. We hypothesized that it is possible to prevent and treat breast cancer by introducing anticancer agents into the mammary ductal network. Here, we show the efficacy of intraductally administered anticancer agents 4-hydroxytamoxifen and pegylated liposomal doxorubicin (PLD) in the prevention and treatment of breast cancer using the rat N-methyl-NV -nitrosourea-induced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 20 publications
2
94
0
Order By: Relevance
“…We recommend practicing this step by injecting trypan blue or some other sterile traceable dye inside of the duct and preparing whole mammary mounts to confirm targeting of the ductal tree. Additionally, other protocols describing intraductal injection of reagents have been published 33,34 , which may be useful for developing proper technique. Issues with viral preparation or infection of the ductal lumen can also be investigated by using a mCherry expressing adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend practicing this step by injecting trypan blue or some other sterile traceable dye inside of the duct and preparing whole mammary mounts to confirm targeting of the ductal tree. Additionally, other protocols describing intraductal injection of reagents have been published 33,34 , which may be useful for developing proper technique. Issues with viral preparation or infection of the ductal lumen can also be investigated by using a mCherry expressing adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a nonsurgical method to reliably diagnose cancer would offer the possibility of diagnosis without surgery in women with PND who have a very low likelihood of significant neoplasia. In the future, a molecular diagnostic test that allows reliable diagnosis of intraductal pathology will enable in situ ablation of benign lesions with either endoscopic techniques or the intraductal administration of antineoplastic agents (19).…”
mentioning
confidence: 99%
“…For example, Okugawa and colleagues showed that rats with N-methyl N'-nitrosourea (MNU)-induced breast tumors exhibited significant reduction in tumor burden and total number of mammary carcinomas when treated with intraductal paclitaxel (27). Similarly, Sukumar and colleagues have shown that intraductal administration of various anticancer drugs, such as pegylated liposomal doxorubicin (PLD), 4-hydroxytamoxifen carboplatin, methotrexate, nanoparticle albuminbound paclitaxel, and 5-fluorouracil was associated with a significant reduction in tumor formation or protected against tumor development in the MNU model, and also minimized the toxic effects of the drugs (28,29). The same group has also shown that in the HER2/neu transgenic mouse (neu-N) model, which spontaneously develops neu-overexpressing multifocal mammary adenocarcinoma beginning at approximately 4 to 5 months of age, intraductal PLD treatment resulted in significantly reduced risk of developing breast tumors.…”
Section: Introductionmentioning
confidence: 96%